2017
DOI: 10.4038/ss.v45i1-2.4696
|View full text |Cite
|
Sign up to set email alerts
|

Inflation Dynamics in Sri Lanka: An Empirical Analysis

Abstract: This paper examines the dynamics of inflation in Sri Lanka

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
2
10
0
5
Order By: Relevance
“…Several theoretical and empirical studies have shown inflation being influenced by both demand- and supply-side factors (Bandara, 1996; Colombage, 2005; Cooray, 2008; Deyshappriya, 2014; Jayawardena & Jayasinghe, 2016; Kulatunge, 2012; Nicholas, 1993; Ratnasiri, 2009; Rupananda, 1994; Weerasekara, 1992). Furthermore, the literature on inflation has discussed, inter alia , inflation persistence across exchange rate regimes (Harischandra, 2007), the magnitude of pass-through rates (Wimalasuriya, 2007), monetary policy impact on growth and inflation (Amarasekara, 2008), inflation–unemployment trade-off (Amarasekara & Bratsiotis, 2015), inflation–output trade-off (Kesavarajah & Middleditch, 2019) and the contribution of oil price (Perera, 2005) and other factors to the inflation in Sri Lanka (De Silva, 2017).…”
Section: Inflation and Foreign Reserves: Brief Review Of The Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Several theoretical and empirical studies have shown inflation being influenced by both demand- and supply-side factors (Bandara, 1996; Colombage, 2005; Cooray, 2008; Deyshappriya, 2014; Jayawardena & Jayasinghe, 2016; Kulatunge, 2012; Nicholas, 1993; Ratnasiri, 2009; Rupananda, 1994; Weerasekara, 1992). Furthermore, the literature on inflation has discussed, inter alia , inflation persistence across exchange rate regimes (Harischandra, 2007), the magnitude of pass-through rates (Wimalasuriya, 2007), monetary policy impact on growth and inflation (Amarasekara, 2008), inflation–unemployment trade-off (Amarasekara & Bratsiotis, 2015), inflation–output trade-off (Kesavarajah & Middleditch, 2019) and the contribution of oil price (Perera, 2005) and other factors to the inflation in Sri Lanka (De Silva, 2017).…”
Section: Inflation and Foreign Reserves: Brief Review Of The Literaturementioning
confidence: 99%
“…The ECT defines how quickly each variable’s deviation in the long-run equation is corrected gradually towards the equilibrium level through a series of partial short-run adjustments (Chaudhry et al, 2011; Kulatunge, 2012). Considering the inflation–reserves nexus, the ECT for CBR depicts that 0.5% of the long-run adjustment of CCPI is envisaged from the partial short-run adjustment of CBR every month.…”
Section: Data Analysis and Empirical Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, Colombo consumer price index (CCPI), wholesale price index (WPI) and gross domestic product deflator (GDPD) are the three major indicators used to measure the changes in the prices in Sri Lanka. According to Kulatunge (2017), CCPI is the official CoL index in Sri Lanka. Furthermore, it says that, CCPI covers a large number of items and is heavily weighted to food items which include 41% of the index.…”
Section: Introductionmentioning
confidence: 99%